2018
DOI: 10.3390/en12010013
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Renewable Energy by Means of Using Residual Forest Biomass

Abstract: The substitution of energy based on fossil fuel by bioenergy could be an effective solution to reduce external energy dependency, thereby promoting sustainable development. This article details a study of the use of biomass residues produced in the forestry sector as a consequence of field operations of the two predominant forest species (Pinus radiata D. Don and Ecualyptus globulus Labill) of Biscay (Spain). The potential of forest residues is estimated to be 66,600 dry Mg year − 1 . These residues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The process of transforming the advanced biofuels and biogas into bioenergy with low emissions of greenhouse gas should be regarded in a cost effective manner, paying attention to the need for development of the corresponding high-tech bioenergy infrastructure [9][10][11][12][13][14]. To streamline the process, the European legislators thought of conceiving thresholds to keep a balance between the need to produce clean energy and biodiversity demands.…”
Section: Introductionmentioning
confidence: 99%
“…The process of transforming the advanced biofuels and biogas into bioenergy with low emissions of greenhouse gas should be regarded in a cost effective manner, paying attention to the need for development of the corresponding high-tech bioenergy infrastructure [9][10][11][12][13][14]. To streamline the process, the European legislators thought of conceiving thresholds to keep a balance between the need to produce clean energy and biodiversity demands.…”
Section: Introductionmentioning
confidence: 99%
“…The factors obtained for M. × piperita L. var. citrata Ehrh.-'Bergamot' (highest emission factors) are comparable with emission factors for oak tree leaves [49] or eucalyptus globulus [2]. However, the examined biomass is not the one with the lowest emission potential.…”
Section: Discussionmentioning
confidence: 65%
“…The market of low-power (from several kW to 2 MW) heating plants fueled with biomass offers many innovative technical solutions. Replacing coal with biomass fuel is beneficial in that it contributes to reducing gas emissions [1]; is an excellent solution for the socio-economic development of disadvantaged areas, rural or peripheral [2]; and has the possibility of being implemented at a large scale [3]. In terms of energy yield, 2 tonnes of biomass is on average an equivalent to 1 tonne of hard coal.…”
Section: Introductionmentioning
confidence: 99%
“…The dust emission index, related to the ash content of the individual raw materials, is the highest for WRON (5.31 kg•Mg −1 ) and the lowest (14% lower) for WSBL (4.57 kg•Mg −1 ). The analysis of the emission factors showed that the analyzed biomass is characterized by higher emission rates relative to mint [46], tree leaves [47], rice straw [48], similar to eucalyptus globulus wood [49] and larch needles [34] and lower relative to jackfruit peel and jackfruit seeds [32]. Nevertheless, in relation to hard coal [33], it is characterized by low emissions in terms of the analyzed factors, which indicates that this fuel as environmentally friendly.…”
Section: Resultsmentioning
confidence: 99%